Co-delivery of NIR-II semiconducting polymer and pH-sensitive doxorubicin-conjugated prodrug for photothermal/chemotherapy - Yu, D; Wang, Y; Chen, J; Liu, S; Deng, S; Liu, C; McCulloch, I; Yue, W; Cheng, D (Elsevier, 2021)
Semiconducting polymer (SP) is a promising photothermal agent in the antitumor application, but the co-delivery of the second near-infrared window (NIR-II)-based SPs with chemotherapeutic drug (e.g., doxorubicin (DOX)) remains a challenge. Here, SPs were firstly improved via backbone and alkyl side-chain engineering, and afterward, SPs and pH-sensitive prodrug copolymer self-assembled into a nanoparticle for a photoacoustic (PA)-imaging guided combination of photothermal therapy and chemotherapy. SP-encapsulated nanoparticles exhibited a high photothermal conversion efficiency of 45% at a relatively low power level of NIR irradiation (0.3 W/cm2 for 5 min). DOX was rapidly released in response to the acidic lysosomal environment. PA and fluorescence imaging confirmed that the photothermal therapy effectively drove DOX penetration inside tumor tissue, and it resulted in the killing of the surviving tumor cells from hyperthermia. The synergistic effect of SP-based photothermal therapy and DOX-induced chemotherapy was verified in vivo. Overall, the co-delivery of the SP and DOX using pH-sensitive nanoparticles represents a feasible strategy for photothermal therapy with potentially synergistic drug effects.